2014
DOI: 10.4067/s0716-10182014000600001
|View full text |Cite
|
Sign up to set email alerts
|

Enfermedad meningocóccica en la Región Metropolitana de Chile y su correlación con factores ambientales

Abstract: Introduction: Meningococcal disease (MD) is a public health problem worldwide, due to its high morbidity and mortality. Most cases occur in sub-Saharan Africa, where there is a marked seasonal pattern with predominance during the dry season. Objectives: To describe the morbidity of MD in the Metropolitan Region (MR) of Chile and explore whether there is a correlation between the number of cases with the levels of atmospheric particulate matter PM 10 and PM 2.5, relative humidity (RH), temperature and total env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…This study found that air pollution had a positive association with the burden of meningitis, which may be related to multiple mechanisms. Air pollution particles may make pathogen colonization possible by reducing mucosal ciliary clearance, reducing the barrier effect of the airways, and dysregulating the airway microbiota, while air pollution may enhance the inflammatory response of the body and enhance the transmission of pathogens such as S. pneumoniae to tissues and blood, causing carriers to be more likely to develop meningitis and resulting in higher ASDRs and ASYRs [ 34 , 35 ]. Before our study, a large body of current research focused on the association between meningitis incidence and dust/pm2.5, and most of the studies were limited to a single country [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that air pollution had a positive association with the burden of meningitis, which may be related to multiple mechanisms. Air pollution particles may make pathogen colonization possible by reducing mucosal ciliary clearance, reducing the barrier effect of the airways, and dysregulating the airway microbiota, while air pollution may enhance the inflammatory response of the body and enhance the transmission of pathogens such as S. pneumoniae to tissues and blood, causing carriers to be more likely to develop meningitis and resulting in higher ASDRs and ASYRs [ 34 , 35 ]. Before our study, a large body of current research focused on the association between meningitis incidence and dust/pm2.5, and most of the studies were limited to a single country [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Se han observado tasas similares en otros países de Latinoamérica, como en Colombia donde la enfermedad diarreica aguda representa la segunda causa más común de morbilidad, con incidencia de 110 casos por 100.000 habitantes 13 . En Perú durante el año 2014, las "Enfermedades Infecciosas Intestinales" (A00-A09) ocuparon el noveno lugar como causa de hospitalización, que correspondió a 1,5% de la totalidad de eventos, observándose que la incidencia muestra una lenta tendencia al descenso, notoriamente más evidente en niños bajo 5 años de edad 14 .…”
Section: Discussionunclassified
“…There are substantial epidemiological differences between the different countries of the region. In Chile, since the epidemic by serogroup W in 2012 and despite vaccination with the conjugate vaccine for serogroups A, C, W, and Y (Men ACWY), serogroup W continues to be the most frequent 11,12 . In Argentina, the most frequent serogroups are B and W, with an increasing trend of the latter since 2008 11 .…”
Section: Introductionmentioning
confidence: 99%